Isolation of Leclercia adcarboxglata Strain JLS1 from Dolostone Sample and Characterization of its Induced Struvite Minerals. Issue 6 (3rd July 2017) - Han, Zuozhen; Sun, Bin; Zhao, Hui; Yan, Huaxiao; Han, Mei; Zhao, Yanyang; Meng, Ruirui; Zhuang, Dingxiang; Li, Dan; Ma, Yutong; Ma, Peiyu; Pan, Juntong
ABSTRACT: The biomineralization of struvites is becoming a very popular research subject. In this study, struvite crystals were precipitated and characterized in the presence of the bacterial Leclercia adcarboxglata strain JLS1 that was isolated from a typical dolostone sample. The JLS1 strain was identified as L. adcarboxglata using physiological and biochemical identification methods and by 16S rDNA phylogenetic analysis. The minerals obtained from the culture medium using experimental samples inoculated with L. adcarboxglata JLS1 were not found in the control samples without the bacteria. The experimentally derived minerals were determined to be pure struvites that exhibited primarily a uniform, prismatic-shaped morphology of various sizes. The results of the X-Ray Powder Diffraction (XRD) analysis of the minerals revealed that the preferred orientation and lattice distortion were characteristic of struvite crystals. In the experiments conducted using the L. adcarboxglata it was also found that the phosphate, ammonium and magnesium ions in solution were consumed to form the struvites in an alkaline environment. The results of this study can provide important insights into the understanding of the biomineralization process of microbial struvites and wastewater treatment applications, as well as the genesis and therapy of kidney stones.